2017
DOI: 10.1038/srep39754
|View full text |Cite
|
Sign up to set email alerts
|

The role of Frenkel defect diffusion in dynamic annealing in ion-irradiated Si

Abstract: The formation of stable radiation damage in crystalline solids often proceeds via complex dynamic annealing processes, involving migration and interaction of ballistically-generated point defects. The dominant dynamic annealing processes, however, remain unknown even for crystalline Si. Here, we use a pulsed ion beam method to study defect dynamics in Si bombarded in the temperature range from −20 to 140 °C with 500 keV Ar ions. Results reveal a defect relaxation time constant of ~10–0.2 ms, which decreases mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…3 alternate between the two simplest decay process equations: the first order ( n ( t off ) = n ∞ + ( n (0) − n ∞ ) exp (− t off / τ 1 )) and second order decay equations. This finding is in contrast to results of our recent pulsed beam study 19 of Si that has revealed a clear switch from the second to the first order decay at a certain T . However, both first and second order fits for Ge shown in Fig.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…3 alternate between the two simplest decay process equations: the first order ( n ( t off ) = n ∞ + ( n (0) − n ∞ ) exp (− t off / τ 1 )) and second order decay equations. This finding is in contrast to results of our recent pulsed beam study 19 of Si that has revealed a clear switch from the second to the first order decay at a certain T . However, both first and second order fits for Ge shown in Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Comparing DA in Ge to that in other semiconductors, we note that our τ values of ~0.3–8 ms in Ge (at 100–160 °C) are similar to those for Si (~0.2–14 ms in a wider T range from −20 to 140 °C), 3 C -SiC ( τ = 3 ms at 100 °C), and 4 H -SiC ( τ of ~1–5 ms at 25–250 °C) recently measured with the pulsed ion beam technique 15 19 . Despite such similarity of the range of the τ values measured, the details of defect interaction dynamics are strongly material dependent.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations